THE EFFECT OF PROFESSIONALISM LEVEL AND INTERNAL CONTROL ON EMPLOYEE PERFORMANCE (Study on Employees of the National Land Agency Regional Office of Bali Province) - Ni Putu Esha Darmayanti; Ni Luh Supadmi (INTERNATIONAL JOURNAL OF ECONOMIC LITERATURE, 2025)
This study aims to examine the relationship between professionalism, internal control, and employee performance. The research was conducted at the Regional Office of the National Land Agency (BPN) of Bali Province, involving a sample of 70 civil servants. The research instrument used was a questionnaire developed based on indicators for each variable. Data analysis was carried out using Structural Equation Modeling (SEM) with the Partial Least Squares (PLS) method. Theories used in this study include professionalism theory and Government Regulation Number 60 of 2008. The results show that both the level of professionalism and internal control have a positive and significant effect on employee performance. The implications of this research are expected to serve as a reference for leaders at the Regional Office of the National Land Agency of Bali Province and other institutions in formulating policies that support the enhancement of professionalism and internal control in government institutions, which in turn can improve employee performance.